(untitled) (Journal of Medical Device Technology, 2024)
Polycaprolactone (PCL) is one of synthetic biomaterials that have been used for bone scaffolds. PCL is a synthetic, linear, and semicrystalline aliphatic polymer that is widely used for bone application due to its biocompatibility and good mechanical properties. However, PCL has disadvantages due to its hydrophobicity nature that require combination with another natural biomaterial such as Gelatin. However, this composite still lacks elements to support bone mineralization environment. Besides hydroxyapatite, ß-tricalcium phosphate (B-TCP) is one of bioceramics that having similar components with natural bone minerals. ß-Tricalcium phosphate (B-TCP) is a widely used for bone scaffolds, but the study on the effect of this biomaterial coating on nanofibers remains limited. Therefore, this study focuses on the surface modification of fabricated PCL/Gelatin nanofibers with B-TCP. Prior to surface modification, PCL/Gelatin nanofibers were fabricated by using an electrospinning at two distinct PCL to gelatin volume ratio, which are 60:40 and 70:30. This approach aims to identify the optimal volume ratio for nanofiber through scanning electron microscope (SEM) result analysis. The PCL/Gelatin nanofibers with mix ratio of 70:30 was selected and subjected to surface modification using a post-treatment method, involving immersion in a B-TCP solution. Following this modification, all types of nanofibers were analyzed using SEM, Fourier transform infrared spectroscopy (FTIR), and water contact angle (WCA) measurements. The surface-modified PCL/Gelatin nanofibers treated with B-TCP (PCL/Gelatin/B-TCP) exhibited a rougher morphology, with an average diameter of 395.0799.83 nm and an average porosity of 26%. WCA analysis indicated an increase in hydrophilicity for the PCL/Gelatin/ß-TCP nanofibers, with an average contact angle of 56.17#2.87°, compared to the PCL/Gelatin nanofibers, which had an average contact angle of 89.958.43°. Based on the results obtained, the surface modified-nanofibers demonstrated characteristics that have potential in enhancing bone regeneration. Consequently, this provides valuable insights for advancing bone tissue engineering applications.